IN–VITRO PROPAGATION AND ANTIMYCOTIC POTENTIAL OF EXTRACTS AND ESSENTIAL OIL OF ROOTS OF ARISTOLOCHIA BRACTEOLATA LINN. (ARISTOLOCHIACEAE) - Gbadamosi, I T; Egunyomi, A (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
In spite of the therapeutic importance of Aristolochia bracteolata Linn. in Nigerian ethnomedicine, it is largely collected from the wild. Owing to the acclaimed potency of the plant and the difficulty in treating candidiasis, the anticandidal activity and in vitro propagation of the plant were investigated. Phytochemical screening and preparation of extracts of the roots were done using standard procedures. Clinical isolates of Candida albicans were screened against extracts and essential oil of Aristolochia bracteolata root using agar-well diffusion method. Minimum Inhibitory Concentration (MIC) of the ethanol extract was determined using broth dilution method. The nodal cuttings of A. bracteolata were cultured on Murashige and Skoog (MS) basal media. A. bracteolata contained alkaloids, saponins and cardenolides. The water extract was inactive on all isolates. The ethanol extract (500 mg/ml) and essential oil (undiluted) exhibited anticandidal activity on 9 out of 10 isolates at 101 – 106 cfu/ml inoculums concentration. Green growth and callus formation were observed in explants cultured on MS basal media after 30 days. A. bracteolata could be a source of anticandidal phytomedicine and the in vitro propagation confirmed its sustainability as anticandidal agent.